HIPERSEMIOTIKA PADA MITOS TENTANG COVID-19 DI MEDIA SOSIAL FACEBOOK DAN WHATSAPP - Tita Sahara (Universitas Prof. Dr. Moestopo (Beragama), 2022)
In the era of the Covid-19 pandemic, myths emerged in the community through the Internet, especially social media Facebook and Whatsapp. In the midst of increasing cases of Covid-19 transmission, the spread of information related to Covid-19 on the Internet can easily and quickly spread in the community. This has resulted in panic leading to belief in myths related to the prevention and treatment of Covid-19 without seeking further information. For example, myths about the efficacy of onions and garlic, cooking lodeh vegetables in Yogyakarta and making wong-wongan rice as ritual to ward off natural disasters and diseases in Bali. This article examines the excessive content of signs in mythical texts. This study aims to understand the signs of hypersemiotics in the myth txt. The study uses a constructivist paradigm with a qualitative approach and descriptive type and uses hypersemiotic theory. Data were collected by documentation study and interviews. The data were analyzed by Yasraf A. Piliang’s hypersemiotic analysis method. As a result, researchers found hyper-signifier and hyper-code in mythical texts. Also the exixtence, meaning and function of hypersemiotic signs in myth